2020
DOI: 10.1002/ejlt.202000129
|View full text |Cite
|
Sign up to set email alerts
|

Partial De‐Stoning of Olive Paste to Increase Olive Oil Quality, Yield, and Sustainability of the Olive Oil Extraction Process

Abstract: Stone recovery in the olive oil extraction process can be an opportunity to increase both incomes and environmental sustainability. To this aim a new partial de-stoning machine (called Moliden) is installed at the first stage of an olive oil extraction plant to investigate its influence on the quality and sustainability of the extraction process. Quantitative and qualitative results are compared with those achieved using a conventional extraction process. Despite the 60% of stone recovered, no significant diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
4
2
0
Order By: Relevance
“…The diameter of the holes and speed of rotation are also technological parameters to be considered during the crushing process, as they determine the thickness of the paste and thus the composition and quality of the final EVOO produced, as investigated by Inarejos-García et al [19]. These results are in accordance with those reported by other authors [14,17,21,22]. The present study entailed a set of experimental tests on a new machine, a new type of modular mechanical crusher developed in partnership with a private company manufacturing machines for the extraction of olive oil.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…The diameter of the holes and speed of rotation are also technological parameters to be considered during the crushing process, as they determine the thickness of the paste and thus the composition and quality of the final EVOO produced, as investigated by Inarejos-García et al [19]. These results are in accordance with those reported by other authors [14,17,21,22]. The present study entailed a set of experimental tests on a new machine, a new type of modular mechanical crusher developed in partnership with a private company manufacturing machines for the extraction of olive oil.…”
Section: Introductionsupporting
confidence: 87%
“…A higher granulometric fraction of KC olive paste entailed a lower level of POX activity during the mechanical extraction process, justifying the higher total phenol content of KC VOOs compared to HC VOO samples due to reduced oxidoreductase activity. The limited activity of POX, due to a mild disruption of the seed tissues or the use of a destoning machine, confirms results on the improvement of the phenolic compounds of VOOs during the mechanical extraction process [17,[37][38][39][40][41]. The new knife rotor, fitted with five overlapping fringes, was able to combine the optimal rupture of the olive pulp necessary for the biogeneration of phenolic compounds , limiting the negative effects due to the oxidation process induced by POX (Luaces et al, 2007;Garcia-Rodriguez et al, 2015) [35,37].…”
Section: Qualitative Evaluationsupporting
confidence: 74%
See 1 more Smart Citation
“…The phenolic concentration of Canino, Coratina, and Peranzana showed an improvement of total phenols of EVOOs extracted from de-stoned olives compared to the control test, with significant increases of 21, 19.7, and 15.8%, respectively (Figure 6). The effect of the destoning process on phenolic content was not influenced by the genotypes, as reported by previous studies [26,29,40]. On the contrary, Criado-Navarro et al [41], in a recent study, showed a differentiated impact on secoiridoid content of Arbequina and Picual cultivars.…”
Section: Nutritional and Nutraceutical Analysissupporting
confidence: 66%
“…The values of the merchandising parameters did not show any significant alteration. The lack of effects on EVOO legal quality parameters has been confirmed by other authors, not only for the de-stoning process but also for new technologies with a high physicalchemical impact on the olive paste tissues [26][27][28][29]. The slight differences detected among the cultivars were not due to the different extraction processes but to the quality index and the different maturity of the olives.…”
Section: Merceological Parameterssupporting
confidence: 54%